Cost-utility analysis of the insufflation of warmed humidified carbon dioxide during open and laparoscopic colorectal surgery. (2nd January 2017) - Jenks, Michelle; Taylor, Matthew; Shore, Judith
ABSTRACT: Background: An evaluation was conducted to estimate the cost-effectiveness of insufflation of warmed humidified CO2 during open and laparoscopic colorectal surgery compared with usual care from a UK NHS perspective. Methods: Decision analytic models were developed for open and laparoscopic surgery. Incremental costs per quality-adjusted life year (QALY) were estimated. The open surgery model used data on the incidence of intra-operative hypothermia and applied risks of complications for hypothermia and normothermia. The laparoscopic surgery model utilised data describing complications directly. Sensitivity analyses were conducted. Results: Compared with usual care, insufflation of warmed humidified CO2 dominated. For open surgery, savings of £20 and incremental QALYs of 0.013 were estimated per patient. For laparoscopic surgery, savings of £345 and incremental QALYs of 0.001 per patient were estimated. Results were robust to most sensitivity analyses. Conclusions: Considering the current evidence base, the intervention is likely to be cost-effective compared with usual care in patients undergoing colorectal surgery.